2011
DOI: 10.1590/s0006-87052011000200028
|View full text |Cite
|
Sign up to set email alerts
|

Adubação nitrogenada na cultura do milho safrinha irrigado em plantio direto

Abstract: A cultura do milho safrinha é uma importante alternativa econômica para a entressafra. Contudo, esta cultura remove grandes quantidades de nitrogênio (N) e necessita de manejo adequado da adubação nitrogenada para obtenção de elevadas produtividades. O objetivo deste trabalho foi avaliar o efeito de fontes, doses e épocas de aplicação de N nas característi-cas agronômicas e na produtividade de grãos de milho safrinha irrigado. O experimento foi realizado em Selvíria (MS), em Latossolo Vermelho Distroférrico, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
1
21

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 10 publications
(3 reference statements)
6
19
1
21
Order By: Relevance
“…The increase in leaf N content, according to Souza et al (2011), increases the grain yield of corn grown after corn up to 150 kg ha -1 of N, regardless of the application before sowing or topdressing and the source ammonium sulfonitrate with nitrification inhibitor, ammonium sulfate or urea. Amaral Filho et al (2005) also observed increases in leaf N content and in estimates of chlorophyll content and yield.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in leaf N content, according to Souza et al (2011), increases the grain yield of corn grown after corn up to 150 kg ha -1 of N, regardless of the application before sowing or topdressing and the source ammonium sulfonitrate with nitrification inhibitor, ammonium sulfate or urea. Amaral Filho et al (2005) also observed increases in leaf N content and in estimates of chlorophyll content and yield.…”
Section: Resultsmentioning
confidence: 99%
“…Amaral Filho et al (2005) also observed increases in leaf N content and in estimates of chlorophyll content and yield. Nevertheless, Hurtado et al (2010) evaluated the nutritional status of corn using a chlorophyll meter and found a need for up to 180 kg ha -1 N, exceeding the amount required to achieve maximum yield with 150 kg ha -1 (Souza et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Na dose de 32,5 kg ha -1 de N a maior média de MSPA foi observada com a utilização da fonte UK enquanto que nas doses intermediárias (65 e 130 kg ha -1 de N) a fonte U foi superior; já na maior dose de N, as fontes UN e UK obtiveram as maiores produções de MSPA; para a variável MCG, somente na dose de 32,5 kg ha -1 de N houve diferenças entre fontes, em que a fonte U obteve maior média. Oliveira & Caires (2003) e Souza et al (2011) também observaram aumentos lineares na MCG com as doses de N em milho. Neste sentido, o aumento das doses de N pode ter favorecido o enchimento de grãos e o aumento da sua densidade.…”
Section: Resultsunclassified
“…Somente na dose de 32,5 kg , estando abaixo do relatado por Silva et al (2011) e Souza et al (2011 para a cultura do milho.…”
Section: Resultsunclassified